Insurance-markets Equilibrium with a Non-convex Labor Supply decision, Unobservable Effort, and Efficiency Wages of the "No-shirking" Type - Aleksandar Vasilev (ZBW – Leibniz Information Centre for Economics, 2018)
The purpose of this paper is to describe the lottery- and insurance-market equilibrium in an economy with non-convex labor supply decision, unobservable effort, and efficiency wages of the no-shirking type a la Shapiro and Stiglitz (1984). The presence of indivisible labor creates a market incompleteness, which requires that an insurance market for (un)employment be put in operation to "complete" the market.
Keywords: E1; J22; J41; 330; indivisible labor; lotteries; unobservable effort; insurance; no-shirking efficiency wages